Islamic Philantrophy and Muhammadiyah’s Contribution to the Covid-19 Control in Indonesia - Muchammad Ichsan (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2020)
Philanthropy is one of the most significant Islamic teachings, and it has been practiced by Muhammadiyah, one of Indonesia 's moderate Islamic organizations. As the pandemic of Covid-19 broke out, many parties — including Muhammadiyah — were motivated to get involved in handling it. This research aims to reveal what Muhammadiyah has done and is currently doing to overcome Covid-19 and the extent of its impact on the wider community. For this purpose, the descriptive-analysis method is employed in its writing. Among the findings of this study is that one of the most consistent Islamic philanthropic organizations since its establishment in Indonesia is Muhammadiyah. In the Covid-19 issue, Muhammadiyah has contributed a lot and continues to take a significant role in overcoming it. Among other things, Muhammadiyah has formed the Muhammadiyah Covid-19 Command Center (MCCC), which is a special team formed to handle Covid-19. This team has been working since it was founded and continues to work on this case. The results of the work included assistance in the field of health that is needed such as providing hospitals, doctors, medical personnel, and medicine. Assistance in the field of education such as making educational media, subsidizing credit for students, and discounting student study fees. And assistance in the social sector such as cash assistance, distribution of groceries, and the provision of free sahur (food before fasting) and takjil (food for breaking fasting) in Ramadhan 1441H. Besides, through the Tarjih and Tajdid Assembly, Muhammadiyah has provided religious guidance for its members during this pandemic so that they are not confused about practicing worship. The impact of these programs and actions is that members of Muhammadiyah, and in general the wider community, are greatly helped in the health, education, social and religious fields.